2013
DOI: 10.1063/1.4776220
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of radio-frequency ring-shaped hollow cathode discharge using H2 and Ar gases for plasma processing

Abstract: In order to achieve high-density capacitively coupled plasma, a radio-frequency (RF) ring-shaped hollow cathode discharge has been developed as a candidate for processing plasma sources. The plasma density in the hollow cathode discharge reaches a high magnitude of 1010–1011 cm−3. The RF ring-shaped hollow cathode discharge depends on the pressure and mass of the working gas. Criteria required for producing a RF ring-shaped hollow cathode discharge have been investigated for various gas pressures using H2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The results have revealed that the trench width must be approximately equal to the sum of the electron-neutral mean free path and twice the sheath thickness of the powered electrode in order to realize the desired effect of the trench on the plasma density. 43 This criterion is conceptually similar to those for the classical hollow cathode effect (HCE) based on similarity parameters. In previous works, however, the influence of the trench depth on plasma parameters was not understood.…”
Section: Physics Of Plasmas 23 033510 (2016)mentioning
confidence: 91%
See 3 more Smart Citations
“…The results have revealed that the trench width must be approximately equal to the sum of the electron-neutral mean free path and twice the sheath thickness of the powered electrode in order to realize the desired effect of the trench on the plasma density. 43 This criterion is conceptually similar to those for the classical hollow cathode effect (HCE) based on similarity parameters. In previous works, however, the influence of the trench depth on plasma parameters was not understood.…”
Section: Physics Of Plasmas 23 033510 (2016)mentioning
confidence: 91%
“…The electron temperature and density as well as the plasma potential are obtained radially resolved from measurements of the current-voltage characteristics of a tiny cylindrical tungsten probe according to Langmuir probe theory 7,52,53 at various trench depths. The probe system is compensated with an L-C parallel circuit 12,26,[30][31][32][33][42][43][44] (choke) in order to avoid any parasitic effects of rf plasma potential oscillations on the probe current-voltage characteristics. At the gas pressure of 53.2 Pa, the electron-neutral mean free path is smaller than the dimensions of the probe and the electron saturation current detected by the probe must be revised.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since in the hollow cathode, electrons are not as easily lost to ground as in the case of the planar magnetron, it is not completely clear how the magnetic field increases ionization. However, the use of magnetic fields has been reported to increase the plasma density and, correspondingly, the plasma current [195][196][197][198][199][200][201][202][203][204].…”
Section: Magnetic Field Effectmentioning
confidence: 99%